GIVE THE CORRECT ANSWER AND I WILL THANK, RATE 5 STARS, AND GIVE BRAINLIEST!!!
System Of Equations:
Solve by substitution:

y = x + 3

7x - y = 3

Group of answer choices

(1 , 4)

(-1 , -4)

(-1 , 4)

(1 , -4)

Respuesta :

Answer:

(1, 4)

Step-by-step explanation:

subsitute y=x+3 into the 2nd equation, which you will get 7x-(x+3)=3

get rid of the (), which you will get 7x-x-3=3

combine like terms and get 6x-3=3

move 3 to the other side and divide both sides by 6 and get x=1

use the first equation y=x+3 and subsitude 1 for x and get y=1+3

y=4

ACCESS MORE